Understanding transparency of government from a Nordic perspective: open government and open data movement as a multidimensional collaborative phenomenon in Sweden. Issue 4 (2nd October 2017) - Kassen, Maxat
ABSTRACT: As the historical homeland of the first freedom of information law, Sweden is universally well-known for its centuries-long traditions of government transparency and respect for individual freedoms and liberties that have been deeply rooted in public mentality of people since medieval times. Today, this nation is also emerging as a global leader in advancing open data phenomena, launching an extremely wide range of public platforms in the sphere. In this respect, this article is mostly presented as a policy review of the open data movement in this Nordic state through the prism of its traditional inclination toward philosophy of open government, open economy, open source software, open science, and even pirate politics. In an attempt to understand a highly context dependable and truly multidimensional nature of the phenomena, the research analyzes various political and socioeconomic backgrounds of the open data movement, tracing interesting patterns and promising networking trends that could be observed today in the communication between its key stakeholders and demonstrating in an intrinsically empirical and illustrative manner how its fundamental pillars such as civic engagement, direct participation and public-private partnerships are exactly promoted within one given society.